PENDIDIKAN ENTERPRENEURSHIP BAGI MAHASISWA - Apriansyah, Andika; Putri Isyara, Larissa; Abdurrahmansyah, Abdurrahmansyah; Handayani, Tutut (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
According to the Central Statistics Agency (BPS), unemployment in Indonesia at the diploma and undergraduate level has reached 9.39% and it is feared that it will continue to increase if many university graduates are less able to direct their students and alumni to create their own jobs. One solution to reduce educational unemployment is to prepare graduates to become independent young entrepreneurs. Unemployment at the tertiary level is also caused by graduates' skill competencies not meeting the needs of the job market. This research uses qualitative methods with a literature approach or literature review. Qualitative research is a research method that aims to gain an understanding of reality through an inductive thinking process. Several things can be concluded in this research, namely that entrepreneurship education and academic support have a positive effect on students' entrepreneurial intentions. Entrepreneurship education in higher education does not only teach students to trade or do business, but students should also be taught to dive directly into the world of entrepreneurship, and have direct contact with people who are involved in the business world so that an entrepreneurial mentality will be formed from this experience.